Zasada fair play jako wsparcie działań profilaktycznych wzmacniających młodzież w kryzysie wartości - Kowalska, Jolanta (Kultura-Społeczeństwo-Edukacja, 2022)
Due to the deficit of the expected young people’s moral attitudes caused, inter alia, by a crisis of values (considered on the one hand in the context of changes related to the age of adolescence, and on the other hand, to social changes), it is worth to support preventive activities. It can be done thanks to the use of the sports fair play principle as – in the indications of many researchers – a universal principle. It is through its proper observance that we can teach making moral choices – as emphasized by Zofia Żukowska. The humanistic values of sport in the spirit of fair play allow for the development of socially acceptable attitudes. They can be the source of the hierarchy of values of a young person, which will guide them in everyday life situations. The aim of the article is to present the educational potential of sport with the principle of fair play as the basis of Olympism promoted by Pierre de Coubertin, the creator of the modern Olympic Games. This can stimulate the educational reflection of teachers and educators in the context of the possibility of conducting preventive activities in schools, especially today, in the crisis of values that affects young people.